2015
DOI: 10.1007/s12020-015-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatic amplifications and deletions in genome of papillary thyroid carcinomas

Abstract: Somatic gene copy number variation contributes to tumor progression. Using comparative genomic hybridization (CGH) array, the presence of genomic imbalances was evaluated in a series of 27 papillary thyroid carcinomas (PTCs). To detect only somatic imbalances, for each sample, the reference DNA was from normal thyroid tissue of the same patient. The presence of the BRAF V600E mutation was also evaluated. Both amplifications and deletions showed an uneven distribution along the entire PTC cohort; amplifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…*p < 0.05, **p < 0.01, ***p < 0.001. ns, not significant. Center, 2015) and with a recent evidence of FN1 genomic amplifications found in a series of aggressive PTCs (Passon et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…*p < 0.05, **p < 0.01, ***p < 0.001. ns, not significant. Center, 2015) and with a recent evidence of FN1 genomic amplifications found in a series of aggressive PTCs (Passon et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…For each tumor, the risk of recurrence was classified as LR or IR in accordance with the 2015 ATA Guidelines for the Management of Adult Patients with Thyroid Nodules and Differentiated Thyroid Cancer (Haugen et al, 2016). BRAF mutational status was determined by Sanger sequencing, as previously described (Passon et al, 2015). PTC histotypes were determined by histopathological examination.…”
Section: Collection Of Thyroid Tissuesmentioning
confidence: 99%
“…In accordance with their function in cell plasticity, DOCK9 and DOCK11 could play roles in cancer and other pathologies. The abnormal expression of DOCK9 has been found in glioblastoma [ 18 ], papillary thyroid carcinoma [ 19 ], tuberculosis [ 20 ], prostate cancer [ 21 ], and pancreatic cancer [ 22 ], and of DOCK11 in testicular carcinoma [ 23 ]. The implementation of methods for studying the expression of DOCK9 and DOCK11 may help validate these alterations in large numbers of patients.…”
Section: Introductionmentioning
confidence: 99%
“…PDE5 inhibitors have also been used for therapeutic treatment [ 10 ]. Passon and colleagues have reported that the copy number of PDE5 is amplified in papillary thyroid cancer (PTC) [ 15 ]. Further, it was reported that variation in the copy number of PDE5 contributes to tumorigenesis and the development of PTC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%